Antibiotic susceptibility and molecular epidemiology of Acinetobacter calcoaceticus–baumannii complex strains isolated from a referral hospital in northern Vietnam. Issue 4 (December 2014) - Van, Trang Dinh; Dinh, Quynh-Dao; Vu, Phu Dinh; Nguyen, Trung Vu; Pham, Ca Van; Dao, Trinh Tuyet; Phung, Cam Dac; Hoang, Ha Thu Thi; Tang, Nga Thi; Do, Nga Thuy; Nguyen, Kinh Van; Wertheim, Heiman
Abstract: Acinetobacter calcoaceticus–baumannii complex is a common cause of hospital-acquired infections (HAIs) globally, remarkable for its high rate of antibiotic resistance, including to carbapenems. There are few data on the resistance of A. baumannii in Vietnam, which are essential for developing evidence-based treatment guidelines for HAIs. Antibiotic susceptibility testing was conducted by VITEK ® 2, and pulsed-field gel electrophoresis (PFGE) was performed on 66 clinical A. baumannii complex isolates recovered during 2009 at the National Hospital of Tropical Diseases (NHTD), a referral hospital in Hanoi, Vietnam. Basic demographic and clinical data were collected and analysed using descriptive statistics. Most isolates came from lower respiratory tract specimens (59; 89.4%) from intensive care unit (ICU) patients [64/65 (98.5%) with available data] who had been admitted to NHTD for ≥2 days [42/46 (91.3%) with available data]. More than 90% of the isolates were resistant to the tested β-lactamase/β-lactamase inhibitors, cephalosporins, carbapenems, fluoroquinolones and trimethoprim/sulfamethoxazole. Moreover, 25.4% (16/63) were resistant to all tested β-lactams, quinolones and aminoglycosides. All isolates remained sensitive to colistin and 58.7% were susceptible to tigecycline. Of the 66 isolates, 49 could be classified into eight PFGE types (A–H). Every PFGE type, except D, had cluster(s) of three or more isolates with a temporal relationship. In conclusion, these data suggest a significant rise in A. baumannii antibiotic resistance in Vietnam. Clustering within PFGE types supports cross-transmission of A. baumannii within the ICU at NHTD. Increased research and resources in optimising treatment, infection control and antibiotic stewardship are needed.